Digitalpreneur Competency Model and Digital Literacy on MSME Business Performance in Jambi Province - Edward Edward; Fitri Chairunnisa; Ade Perdana Siregar (Dinasti Publisher, 2023)
The development of digital technology opens up opportunities for Micro, Small and Medium Enterprises (MSMEs) to be able to improve their business performance through market expansion and increased sales. Provision of capabilities with digitalpreneur competencies and digital literacy will create successful business actors. The success of business actors can determine the success of their business by achieving business performance in achieving business goals. The aims of this study are (1) to analyze the influence of digitalpreneur competencies on MSME business performance; (2) analyze the influence of digitalpreneur competence on digital literacy; (3) analyzing the influence of digital literacy on MSME business performance; (4) analyze the role of digital literacy in mediating the influence of digitalpreneur competence on MSME business performance. The data analysis method used is Structural Equation Modeling (SEM) measurements using SmartPLS software. The results of the study show that (1) digital literacy shows a significant positive effect on MSME business performance, it is proven that the higher the digital literacy of business actors, the MSME business performance will increase; (2) digitalpreneur competence shows a significant positive effect on MSME business performance, it is proven that the better the digitalpreneur competency owned by business actors, the MSME business performance will increase; (3) digitalpreneur competence shows a significant positive effect on digital literacy, the better the digitalpreneur competence owned by business actors, the better digital literacy will be; (4) digital literacy as a mediation of the influence of digitalpreneur competence shows a significant positive effect on MSME business performance, where digital literacy is considered a variable that strengthens digitalpreneur competence in improving business performance.